2017
DOI: 10.1039/c7ob02406a
|View full text |Cite
|
Sign up to set email alerts
|

Highly regioselective gold-catalyzed formal hydration of propargylic gem-difluorides

Abstract: Herein, we report a highly regioselective gold-catalyzed formal hydration of propargylic gem-difluorides. Not only does this transformation provide access to versatile fluorinated building blocks that were difficult or hardly possible to access beforehand, but it also represents a rare case of a highly regioselective gold-catalyzed hydroalkoxylation of internal alkynes and puts forward the utility of the difluoromethylene unit as a directing group in catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 81 publications
0
34
0
Order By: Relevance
“…In the course of synthesizing 17, we isolated the 3,3-difluoroketones 14 and 23, which are potentially useful building blocks for a variety of applications, but are notoriously difficult to prepare. 42 By combining deoxofluorination and desulfurative fluorination strategies, we installed the (gem-CF 2 ) fragment in the presence of the ketone rather than hydrating a propargylic gem-difluoride to form a ketone. Thus, our synthetic strategy expands the scope of the double di-fluorination of 1,3-diketones and provides an alternative route to the synthesis of 3,3-difluoroketones using accessible and scalable chemistry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the course of synthesizing 17, we isolated the 3,3-difluoroketones 14 and 23, which are potentially useful building blocks for a variety of applications, but are notoriously difficult to prepare. 42 By combining deoxofluorination and desulfurative fluorination strategies, we installed the (gem-CF 2 ) fragment in the presence of the ketone rather than hydrating a propargylic gem-difluoride to form a ketone. Thus, our synthetic strategy expands the scope of the double di-fluorination of 1,3-diketones and provides an alternative route to the synthesis of 3,3-difluoroketones using accessible and scalable chemistry.…”
Section: Resultsmentioning
confidence: 99%
“…In both works by Stepanov et al 36 and Wang et al, 40 propargylic gem-difluorides. 42 This approach installs the (gem-CF 2 ) fragment before the ketone, suggesting that β-ketones deactivate deoxofluorinations.…”
Section: Introductionmentioning
confidence: 99%
“…In the course of synthesizing 17 , we isolated the 3,3-difluoroketones 8 , 14 , and 23 , which are potentially useful building blocks for a variety of applications. 43 By combining deoxofluorination and desulfurative fluorination strategies, we installed the hominal bis( gem -CF 2 ) fragment in the presence of the ketone rather than hydrating a propargylic gem -difluoride to form a ketone. Thus, our synthetic strategy expands the scope of the double difluorination of 1,3-diketones and provides an alternative route to the synthesis of 3,3-difluoroketones using accessible and scalable chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…3,3-Difluoroketones themselves are attractive building blocks but are difficult to synthesize; however, recent work by Hamel et al demonstrated the synthesis of 3,3-difluoroketones via a regioselective gold-catalyzed formal hydration of propargylic gem-difluorides. 43…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of compound 15 with a gold catalyst in the presence of MeOH, followed by hydrolysis, provided ketone 35 in 91% yield (Scheme 3a). 35 The construction of indole 36 through Larock's approach 36 by a reaction of the alkyne 15 with 2-iodoaniline proceeded smoothly (Scheme 3a). Besides, the alkyne could be employed to generate difluoromethylated isoxazole 37 through [3+2] cyclization (Scheme 3b).…”
Section: Synthetic Utilitymentioning
confidence: 99%